The Effectiveness of E-Book App Story Telling of Traditional Game Story Series to Increase the Attachment between Parents and Children - Nofrans Eka Saputra; Yun Nina Ekawati (Universitas Ahmad Dahlan, 2021)
The involvement of parents to tell story to the children takes important role to increase attachment. This research aimed to figure to examine the effectiveness of traditional game story series e-book app to increase the attachment between parents and children. The method used was quasi experiment with pre-post control group design. The population of this research consists of 32 kindergarten students which were split to experimental group and controlled group.Â The experimental group was given storytelling treatment through e-book app series. To measure the result, there was attachment scale used in pretest and posttest. The data was analyzed by using independent t test sample and paired t test sample. The result of the research showed that there was significant attachment between pretest and posttest score within experimental group. Meanwhile, within the controlled group, no significant attachment was found. It can be concluded that traditional game story e-book series can increase the attachment between parents and children. The result of this research supports the previous research conducted by Frude & Killick (2011) which explains that the story telling done by parent to the children increase the attachment.Â Keywords: storytelling, parent and children attachment.Â